Nutritional Status Correlated with Frailty Among Elderly - Dewi, Ucik Yusinta; Mashfufa, Erma Wahyu; Aini, Nur; Martha, Ollyvia Freeska Dwi; Ariani, Tutu April; Haikal, Muhammad; Sari, Yeni Kartika (Journal of Ners and Midwifery, 2025)
Nutritional status is a critical issue for older adults and is closely linked to various health problems. Insufficient or excessive dietary intake can impair the body’s ability to manage physical disorders and diseases, leading to increased weakness in this population. This research aimed to analyze the correlation between nutritional status and frailty in the elderly. This research utilized a cross-sectional design, employing consecutive sampling to gather data from 65 patients in four nursing homes. Participants were elderly individuals over 45 years old, residing in nursing homes, cooperatives, and willing to participate. Sample size determination was performed using G*power 3.1.9.7 software, with a medium effect size of 0.41, a p-value of 0.05, and a power of 0.90. Non-parametric tests were used for data analysis, employing the MNA-SF and Frailty Index Questionnaire-40 (FI-40) instruments. The average age of participants was 75.92 (+9.45) years, with the majority of the sample being elderly, and women constituted 80% of all participants. There was a significant correlation between nutritional status and frailty (p=0.005 <0.05), with a moderate negative relationship (r=-0.344). This research concluded that the better the nutritional status, the lower the frailty level. This research indicated that better nutritional status was linked to reduced frailty in the elderly, highlighting the need for healthcare teams to implement strategies that enhance patient adherence in managing factors that negatively affect nutrition.